Pengaruh Insektisida Nabati dan Kimia terhadap Hama Thrips dan Hasil Kacang Hijau - Indiati, S. W. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
Thrips, Megalurothrips usitatus, is an important pest of mungbean at its vegetative phase. Severe attacks of the pest can cause yield losses of mungbean from 13 to 64 %. An experiment was conducted at Muneng Research Station, Probolinggo, East Java, in dry season of to 2010, to identify effectiveness of biological and chemical insecticides to control thrips. The trial was arranged in a randomized block design with 10 treatments and three replications. The treatments were: spraying with water suspensions of fipronil 2 ml/l, imidaklorprit 200 SL 2 ml/l, imidaklorprit 100 EC 2 ml/l, emamektin benzoate 2 g/10l, neem seed powder (SBM) 100 g/l, garlic bulb extract 85 g/100 ml, ginger rhizome extract 50 g/l, papaya leaves extract 50 g/l, and a mixture of extracts from 25 g green chilies, 25 g ginger, and garlic 50 g/3l. The results showed that the use of SBM, garlic, ginger, papaya, and extracts a mixture of LBJ had an equal effectiveness in suppressing population and intensity of thrip attacked on mungbean. The biologcal insecticides were less effective than the synthetic ones in controlling population and intensity of thrips attacked, but they were safe for the environment. The pesticide treatments reduced yield losses of mung bean up to 63%, depending on the pesticide used.